Solution casting effect of PMMA-based polymer electrolyte on the performances of solid-state electrochromic devices - Abdelhamed, Abdelrahman Hamed Ebrahem; Thien, Gregory Soon How; Lee, Chu Liang; Au, Benedict Wen Cheun; Tan, Kar Ban; Murthy, H. C. Ananda; Chan, Kah Yoong (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Electrochromic devices (ECDs) are devices that change their optical properties in response to a low applied voltage. These devices typically consist of an electrochromic layer, a transparent conducting substrate, and an electrolyte. The advancement in solid-state ECDs has been driven by the need for improved durability, optical performance, and energy efficiency. In this study, we investigate varying the temperature to the casting solution for polymethylmethacrylate (PMMA)-based electrolytes for solid-state ECDs with a structure of glass/ITO/WO3/PMMA electrolyte/ITO/glass. The electrochromic layer, composed of WO3, was deposited using the sol-gel method, while the electrolyte, comprising lithium perchlorate (LiClO4) in propylene carbonate (PC) with PMMA, was prepared via solution casting. Various electrolyte samples were heated at different temperatures of 25, 40, 60, 80, and 100 °C to analyze the impact on the devices’ performance. Our findings indicate that the devices with electrolytes at 25 °C exhibited superior anodic and cathodic diffusion. An increase in heating temperature corresponded with an increase in switching time. Notably, the sample heated at higher temperatures (60, 80, and 100 °C) demonstrated exceptional cycle stability. Nevertheless, samples with higher temperatures displayed a decrease in optical modulation. Additionally, the 100 °C sample exhibited the highest coloration efficiency compared to other samples at lower temperatures. This research highlights the potential of varying the temperature of solution casting on PMMA-based electrolytes in optimizing the performance of solid-state ECDs, particularly regarding coloration efficiency and durability.